An Early Permian brachiopod–gastropod fauna from the Calytrix Formation, Barbwire Terrace, Canning Basin, Western Australia - Taboada, Arturo Cesar (2015)
A small brachiopod–gastropod fauna from a core close to the base of the Calytrix Formation within the Grant Group includes the brachiopods Altiplecus decipiens (Hosking), Myodelthyrium dickinsi (Thomas), Brachythyrinella narsarhensis (Reed), Neochonetes (Sommeriella) obrieni Archbold, Tivertonia barbwirensis sp. nov. and the gastropod Peruvispira canningensis sp. nov. The fauna has affinities with that of the late Sakmarian‒early Artinskian Nura Nura Member directly overlying the Grant Group in other parts of the basin but, as with all lower Cisuralian (and Pennsylvanian) glacial strata in Western Australia, its precise age remains poorly constrained, especially in terms of correlation to international stages. Although the Calytrix fauna lies within the Pseudoreticulatispora confluens Palynozone, the only real constraint on its age (and that of the associated glacially influenced strata) is from Sakmarian (Sterlitamakian) and stratigraphically younger faunas. A brief review of radiometric ages from correlative strata elsewhere in Gondwana shows that those ages need to be updated. The presence of Asselian strata and the position of the Carboniferous‒Permian boundary remain unclear in Western Australia.